Notes on the marine algae of the International Biosphere Reserve Seaflower, Caribbean Colombia VI: New records of Phaeophyceae from Old Providence and Santa Catalina. (2017)
Two species of brown algae (Phaeophyceae), Bachelotia antilarum (Grunow) Gerloff and Dictyota humifusa Hörnig, Schnetter and Coppejans, are reported for the first time for the Archipelago of San Andrés, Old Providence and Sainte Cataline, part of the International Biosphere Reserve Seaflower.